Penilaian Efektivitas Fungsi Kepolisian dalam Penanggulangan Kekerasan terhadap Anak: Studi Kasus di Polrestabes Kota Makassar - Syah, Syamsoe Alam; Pawennei, Mulyati; Zainuddin, Zainuddin (CV. Social Politic Genius (SIGn), 2024)
This research aims to identify and analyze the effectiveness of the police function, and the factors influencing this effectiveness, in combating criminal acts of violence against children. This study falls under the category of empirical legal research, emphasizing field research supported by data and interview results. The research was conducted in Makassar City. The findings indicate that both non-penal and penal measures undertaken by the Makassar City Police Headquarters are considered effective in combating criminal acts of violence against children. Furthermore, eight factors related to these non-penal and penal measures were identified: legal structure, legal substance, legal culture, legal knowledge, legal awareness, facilities and infrastructure, social environment, and family economy. However, these factors were assessed as having a limited influence on the efforts to combat criminal acts of violence against children occurring in Makassar City. It is recommended that the police optimize their penal and non-penal efforts while concurrently addressing the factors influencing their performance and function, in order to minimize criminal acts of violence against children in the future.